Intimate partner violence and maternal health services utilization: Evidence from 36 National Household Surveys - Leight, Jessica; Wilson, Nicholas (BMC, 2021)
High rates of maternal mortality and intimate partner violence (IPV) are both major worldwide health challenges. Evidence from single-country samples suggests that IPV may be an important risk factor for low utilization of maternal health services, but there is little large-scale evidence on this association. This paper evaluates whether IPV is a risk factor for low utilization of maternal health services in a large cross-country sample, and also compiles evidence on the relative effects of different forms of IPV.